2017
DOI: 10.1016/j.eats.2017.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Transfer of the Long Head of the Biceps Brachii for Anterior Shoulder Instability

Abstract: In the treatment of anterior shoulder instability, there are various conditions in which a sling effect is needed to enhance anterior stability. The traditional Latarjet procedure provides a sling effect but destroys the coracoacromial arch, which may result in superior instability. To preserve the coracoacromial arch and create a sling to enhance the anterior-inferior side of the shoulder, we introduce an arthroscopic technique to transfer the long head of the biceps (LHB) brachii. Indications of LHB transfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 32 publications
0
41
0
Order By: Relevance
“…The main difference between our technique and Collin et al. 16 and Tang and Zhao's 15 is the transposition of the tendon. The graft is placed and fixed perpendicular to the glenoid rim to create a mostly dynamic stabilization effect as in the Bristow procedure.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The main difference between our technique and Collin et al. 16 and Tang and Zhao's 15 is the transposition of the tendon. The graft is placed and fixed perpendicular to the glenoid rim to create a mostly dynamic stabilization effect as in the Bristow procedure.…”
Section: Discussionmentioning
confidence: 79%
“…Several authors proposed the use of dynamic stabilization by transposition of the long biceps head tendon for additional stabilization in the repair of Bankart injury and fixation in the bone channel with the suture button or Bio-Tenodesis anchor. 15 , 16 Other authors showed the effectiveness of a labroplasty with an allograft or autograft. 17 Nicola 18 described transposition using the long head of the biceps through the bone tunnel in the humeral head for shoulder stabilization.…”
mentioning
confidence: 99%
“…Labral proprioception can also play an important and neglected role in shoulder stability 16 . We suggest that the described procedure and similar procedures17, 18 will add not only biomechanical stabilization 19 but also tendon proprioception of the LHB, and the subscapularis can also play an important role in shoulder stabilization.…”
Section: Discussionmentioning
confidence: 99%
“…Technically, it is very difficult to combine this technique with a bone block. LHB transfer for capsular reinforcement has been described by several authors, and it improves results 8, 9. Our idea was to create a technique that combines the advantages of 2 techniques—iliac crest bone grafting and transposition of the LHB parallel to the bone block through the subscapular split.…”
Section: Discussionmentioning
confidence: 99%
“…To solve this problem, we proposed combining this technique with soft-tissue reinforcement and a simultaneous dynamic stabilization technique. A repair technique using the long head of the biceps (LHB) with trans-subscapular tenodesis to the scapular neck has been described by several authors 8, 9. This technique can significantly reinforce the capsular deficit.…”
mentioning
confidence: 99%